Comparison of Bolus Intravenous Lidocaine Administration with Continuous Intravenous Lidocaine on the Incidence of Postextubation Cough in Thyroidectomy Postoperative Patients - Fuadi, Iwan; Zulfariansyah, Ardi; Hallis, Ignatia Karina (Migration Letters, 2024)
Background: Post-extubation cough following thyroidectomy is a dreadful complication. Intravenous lidocaine has been chosen by many as a prophylactic measure. This study aims to compare bolus vs continuous intravenous lidocaine administration on the incidence of postextubation cough in patients after thyroidectomy. Methods: This study was an experimental study with a double blind randomized controlled trial design. Cough incidence was assessed using the original Minogue scale. The study was conducted at Dr. Hasan Sadikin General Hospital Bandung on 40 thyroidectomy patients. Statistical analysis of numerical data used unpaired T test and Mann Whitney while categorical data used Fisher’s Exact Test. Results: The incidence of cough was higher in group A bolus compared to group continuous intravenous lidocaine, with significant statistical difference (p value <0,05) at 12 and 24 hours after extubation. . Conclusion: Continuous intravenous lidocaine is proven to be more effective in reducing the incidence of postextubation cough after thyroidectomy.